PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS TEKS REKON SISWA KELAS V SD - Firly Ilya Mazidah; Ira Eko Retnosari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the effect of the Think Talk Write (TTW) model on the writing skills of fifth grade students in Indonesian language subjects in elementary schools. This study applies a quantitative research with the True Experimental Design method, involving the manipulation of independent variables and random assignment of participants to experimental and control groups using the Pretest-Posttest Control Group Design research design. The population for this study were grade V students of SDN Sedatigede 2, totaling 84 students with a sample of 54 students. This study utilized two classes, namely class VA as the control class and for the experimental class, namely class VB. The data collection instrument utilized the pretest posttest. The data analysis technique used normality test, homogeneity test, and T-test. The result of this study is that there is an effect of TTW model on the writing skills of recon text as evidenced by the pre-test value of 58.65 and the post-test value of 71.05. There is a difference in the test results of the ability to write recon text between students before and after being treated with the TTW model with a Sig. (2-tailed) of 0.00 <0.05 which means H0 is rejected while Ha is accepted. Based on the test results above, a conclusion can be draw that there is an effect of the TTW learning model on the recon text writing skills of grade V students at SDN Sedatigede 2.